Kesesuaian Pemanfaatan Ruang Kecamatan Peukan Bada Berdasarkan RTRW Kabupaten Aceh Besar Tahun 2012-2032 - Alfian Bhara Juang T.A; Fahmi Aulia; Elysa Wulandari (Universitas Syiah Kuala, 2021)
Population growth of 3.77% in a period of 10 years in Peukan Bada District has the impact of changing the use of space from previously agricultural land to built-up land in the form of housing and other supporting facilities. This can affect the suitability of spatial use in 2020 to the spatial use of the Regional Spatial Plan (RTRW). The purpose of this study is to identify the suitability of the spatial use of Peukan Bada Sub-district in 2020 to the spatial use of the Aceh Besar District RTRW in 2012-2032 and identify factors that encourage the suitability of the use of the space. The approach used is descriptive quantitative, analytical method to identify suitability of space utilization using supervised classification method with Maximum Likelihood Classification (MLC) algorithm and then overlay method using ArcGIS 10.8. To see the factors that encourage the suitability of space utilization using the Partial Least Square (PLS) method. The results showed that there were 2 classifications of suitability for spatial use in Peukan Bada District in 2020, namely the classification according to the area of 3046.2 Ha (84%) and the classification not according to the area of 578.8 Ha (16%). Factors that affect the suitability of space utilization are population density, land price, population growth ratio, rainfall and the number of new housing units.